The value of shear wave elastography in the quantification of corpus cavernosum penis rigidity and its alteration with age. Issue 89 (April 2017) - Inci, Ercan; Turkay, Rustu; Nalbant, Mustafa Orhan; Yenice, Mustafa Gurkan; Tugcu, Volkan
Highlights: Shear wave elastography is a new method that can calculate tissue stiffness. The structure of corpus cavernosum is mainly responsible for erectile function. The corpus cavernosum rigidity can be used to evaluate tissue structure. Shear wave elastography can provide information regarding penile structure. Abstract: Objective: The goal of this study was to measure corpus cavernosum (CC) penis rigidity with shear wave elastography (SWE) in healthy volunteers and to evaluate the change of rigidity with age. Methods: SWE was performed in 60 healthy volunteers (age range 20–71, mean 47 ± 12, 83 years). Volunteers were divided into 2 groups by age (Group 1 age <50, group 2 age ≥50). We assessed SWE in 3 parts of penis (proximal, middle and glans penis) on both sides of CC. All values of SWE (in kilo Pascal) were noted along with volunteers' ages. The measurements were done both with transverse (T) and longitudinal (L) sections. We compared all SW values of penis parts and their alterations with age. Results: The shear wave elastography values of CC penis increased with increasing age (p < 0, 01). There was no significant difference between both sides of CC penis (p < 0, 05). We calculated no significant difference between T and L sections of all parts of penis (p < 0, 05). Conclusions: SWE can provide noninvasive quantitative data of CC penis rigidity and its alteration with age. These data may create a new approach in the evaluation process and treatment options for penile pathologies.